Establish of research universities in Malaysia, - Shuib, Munir; Pandian, Ambigapathy (National Higher Education Research Institute, Universiti Sains Malaysia, 2004)
In 2004,Ministry of Education formed an Ad Hoc committee comprising research from universiti Malaya (UM),Universiti Sains Malaysia (USM),Universiti Kebangsaan Malaysia (UKM),and Universiti Putra Malaysia (UPM) to formulate the establish of research university (RUs).